The Asta-Ja Environmental and Natural Resources Policy Framework (Asta-Ja ENRPF) for Sustainable Development in Nepal - Poudel, Durga (Journal of Comparative International Management)

(untitled) (None, 2009)
Effective policy measures are necessary for sustainable utilization, conservation, and development of environmental and natural resources. In order to formulate effective policies, it is important to have a theoretically grounded, holistic, inclusive, science-based, collaborative, forward looking, and systematic policy framework. This paper presents the Asta-Ja Environmental and Natural Resource Policy Framework (Asta-Ja ENRPF) consisting of Asta-Ja policy guidelines and the Asta-Ja policy cycle for sustainable environmental and natural resources development and socioeconomic transformation in Nepal.